BUSINESS RELATIONSHIP DEVELOPMENT IN THE CONTEXT OF A HIGH-RISK AND UNCERTAINTY - Sulhaini Sulhaini (Universitas Hayam Wuruk Perbanas, 2012)
This paper aims to explore how relationship elements fluctuate and business relationshipsdevelop in a volatile country market. Previous studies explored business relationship developmentin stable country markets ignoring the complexity of building relationships in thecontext of high-risk and high uncertainty environment. This study followed the traditions ofinductive logic and used a qualitative approach and multi-case study design. Data was analyzedfollowing the procedure of General Inductive Approach (GIA).The findings suggest thatlearning orientation is a key orientation influencing a companies’ ability to develop businessrelationships in a high- risk country market and that relationships need to be understoodfrom this perspective rather than simply a relational one. Business relationship developmentin a volatile market can be better understood through the learning perspective than merelywithin the relational perspective. Practical implication of the study is that when exporting toa high risk country market, a company needs to develop its orientation towards learning todevelop its ability and capacity to manage and develop business relationships.